Biological control of the citrus leafminer 25 years after its introduction in the Valencia citrus growing area (Spain): a new player in the game - Mansour, D; Pérez-Hedo, Mertixell; Catalán, José; Karamaouna, F.; Braham, M.; Jaques, Josep A.; Urbaneja, Alberto (Elsevier, 2021)
Natural enemies have been the key factor for the regulation of the citrus leafminer populations, Phyllocnistis citrella, since its introduction in Spain in 1993. The use of various broad-spectrum insecticides in citrus has been banned in recent years. This has led to an increase in the abundance and importance of the complex of generalist predators that inhabit the citrus canopy. In this work, we hypothesize that the incidence of P. citrella and the impact of its natural enemies would have changed due to the greater presence of generalist predators. Following the same protocols used in previous studies, three orchards located in Valencia, the major citrus-growing area of Spain, were monitored during 2017-2018. The incidence of P. citrella has decreased from 1.8-2.4 mines per leaf in 2006 to 0.93-1.98 in 2017-2018. This decrease could be attributed to the 43.0% increase of mortality by natural enemies compared to 2006. Currently, predation is the most important mortality factor. Predation resulted in 50.6% of the mortality caused by natural enemies compared to 34.6% in 2006. The first larval instar was the most susceptible to predation. Among the predators collected, the density of Pilophorus clavatus, a zoophytophagous mirid recently detected in Spanish citrus, was positively correlated with P. citrella predation. In the laboratory, females of P. clavatus preyed actively on second-instar P. citrella. Our results show the importance of conservation biological control in Spanish citrus and suggest that P. clavatus is occupying an important niche for the biological control of P. citrella.